Growth, Trade, and Systemic Leadership. - Thompson, William R. (University of Michigan Press, 2009)
Using a "lead economy" approach, Reuveny and Thompson link question about the global trade system to debates about hegemonic stability and the balance of power in world politics. By focusing on economic growth, protectionism, and trade, they surpass hegemonic stability interpretations of international politics to explain not only how hegemons maintain political order, but also the source of hegemonic/systemic leadership, the rise and decline of leadership over time, and the role of system leaders in generating worldwide economic growth and international political economic order. Rafael Reuveny is Associate Professor in the School of Public and Environmental Affairs at Indiana University. William R. Thompson is Professor of Political Science at Indiana University.